Transporte público e mercado imobiliário : uma análise da relação entre acessibilidade e preço dos imóveis - Guilherme Araújo Grochowski (2023)
Due to their widespread use and ease of implementation, bus transportation systems are the most common and perhaps the most important providers of urban accessibility, connecting various points within cities ranging from medium-sized cities to megalopolises in a relatively inexpensive manner. The link between land value and accessibility to public bus transportation has received relatively little research attention, despite its long-known associations. This is due to the difficulty of quantifying and qualifying such a relationship, given its inherent complexity with multiple dimensions and underlying variables. This study proposes the application of regression methods to better understand the relationships between land value and transportation accessibility in the context of Belo Horizonte. The methods employed are Geographically Weighted Regression (GWR) and Hedonic Regressions. Few statistically significant relationships were found between the two variables: accessibility to bus transportation and land value. However, the study explored the relationships of hedonic variables with transportation, contributing to a greater understanding of the relationship between accessibility and land value, which is a major driver of urban development. The main contribution of this study lies in the application of the GWR method combined with hedonic regressions in the context of Land Use and Transportation interaction, demonstrating the validity and limitations of these approaches. Among its findings is that even in an adverse context, where the improvement of the bus transportation system is not specifically aimed at generating urban development or directing the real estate market, it can still generate a modest contribution to land value.